Artificial Intelligence and Information Literacy: A Comparison of Methodology - Zak, Elizabeth (Journal of Multidisciplinary Research Advancements, 2025)
Artificial intelligence, also known as AI, is a current and effective tool. Although professionals across disciplines agree that artificial intelligence may solve problems, its effectiveness information in education is underexplored. Furthermore, understanding how artificial intelligence may relate to information literacy is essential to utilising it properly in matters of misinformation identification. This study seeks to evaluate information literacy suggestions made by AI bots, comparing them to a common and practical information literacy method. Presenting a comparison between current literacy methods and those introduced by AI bots allows researchers and educators to better understand the overlap between the two, as well as identify any differences. Evaluation of current artificial intelligence descriptions of information literacy shows that accuracy and authority are cited as the most valuable elements when assessing the truthfulness of information. While artificial intelligence provides many opportunities for growth, we must better understand its current capacity to educate.